Permanent-income inequality - Brant Abbott; Giovanni Gallipoli (Queen's University, Department of Economics, 2019)
We characterize the distribution of permanent-income and quantify the value of assets and human capital in lifetime wealth portfolios. We estimate the distribution of human wealth using nonparametric identification results that allow for state-dependent stochastic discounting and unobserved heterogeneity. The approach imposes no restrictions on income processes or utility. Accounting for the value of human capital delivers a different view of inequality: (i) in 2016 the top 10% share of permanent-income was 1/3 lower than the corresponding share of assets; (ii) however, since 1989, the top 10% share of permanent-income has grown much faster than the corresponding share of assets. Human wealth has a mitigating influence on inequality, but this effect has waned over time due to the growing importance of assets in lifetime wealth portfolios. We find that consumption expenditures are tightly linked to permanent-income; however, liquidity constraints can lead to substantial deviations below permanent-income.
Keywords: E2; E21; D31; I24; 330; Wealth; Human Capital; Permanent Income; Consumption; Inequality